Latest developments in designing advanced lubricants and greases for electric vehicles—An overview. (22nd May 2022) - Shah, Raj; Gashi, Blerim; Rosenkranz, Andreas
Abstract: According to the Environmental Protection Agency, transportation is the largest contributor of greenhouse gas emissions (28% of total emissions). Electric vehicles have remarkably grown in popularity and represent a greener future for the automotive industry. This growth has prompted lubricant and grease technology to adapt to an entirely new environment, which is exposed to new factors including external electric currents/fields and extreme temperatures and pressures originating from electric motors and power electronics. Consequently, novel lubricants and greases need to be developed and explored to ultimately improve fuel efficiency and performance. Nano‐additives have offered exceptional opportunities to enhance electrical, thermal and tribological properties of the lubricants and greases used. It is thus vital to fully explore and understand the effects of nanoparticles' addition to lubricants and greases, as well as the mechanisms by which improvements are obtained. This perspective summarises the recent trends of developing lubricants and greases for electric vehicles.